Analysis of court decisions concerning the motivation as procedural guarantee (Legal journal - Research in Legal and Social Sciences, 2021)
The sentencing court is the jurisdictional body that is in charge of the substantiation and decision in those cases that have followed their ordinary course until the stage of the oral and public trial, after an accusation presented by the Public Ministry or a private complaint in the cases of crimes of private criminal action. Within this judicial organization, the jurisdictional function of pronouncing a conviction or acquittal arises, duly motivated in accordance with the facts and current regulations. The motivation of the sentences, according to art. 125 of the criminal procedure code must contain a clear and precise justification of the decision and article 398, num. 2) states that they must be presented with the vote of the judges on each of the questions raised in the deliberation, with an exposition of the reasons of fact and law on which they are founded, this in turn, consists of the justification of the sentence embodied in the judicial resolution, a procedural act that essentially represents and gives life to the jurisdictional power. To corroborate the exposed extremes, in the final part, judicial decisions of the sentencing courts of the City of Asunción corresponding to the year 2021 were studied, of punishable acts that occurred between the years 2017 to 2019, which allowed the complete approach of what was established in the articles mentioned and the doctrines developed. For the study, three judicial decisions from 2021 were randomly chosen from the digitized resolutions section of the electronic file system of the Supreme Court of Justice, corresponding to events that occurred between the years 2017 to 2019, which were studied accordingly, qualitative way.
Keywords: motivation; sentences; court; justification; guarantee